Capitol betrayal : a novel - Bernhardt, William, 1960- (New York : Ballantine Books, 2010)
When a malevolent foreign dictator hacks into the U.S. nuclear defense system, the president comes under fire. With the clock winding down, lawyer Ben Kincaid has precious little time to defend the president. While Kincaid faces the trial of his life, legendary CIA agent Seamus McKay races through the clogged streets of Washington, searching for a hidden command center--guarded by murderous fanatics--that now controls U.S. ballistic missiles.
Keywords: National security -- United States -- Fiction; Washington (D.C.) -- Fiction; Political fiction; Suspense fiction